Dynamics and stabilization mechanisms of amorphous solid dispersions - Wanemark, Joel (My University, 2016)
A growing problem in the pharmaceutical industry is the poor water-solubility of new candidate drugs. It is estimated that 75% of drugs under development are considered to have poor water-solubility19, and a low solubility heavily diminishes the chance of drug uptake and therapeutic effect. A method that has received attention lately to achieve increased solubility is to make use of a formulation strategy known as an amorphous solid dispersion (ASD). The amorphous state of the pharmaceutical eliminates the impact of lattice energy resulting in increased solubility. However, since the pharmaceutical is in its thermodynamically metastable amorphous state, the dispersion may crystallize over relevant pharmaceutical timescales thus cancelling the solubility advantage. Stabilizing amorphous pharmaceuticals with polymers in ASDs have proven possible in previous studies, although the stabilization has been attributed to different mechanisms. In this work, the relationship between anti-plasticization effects and hydrogen bonding was investigated in ASDs with ibuprofen and felodipine using dielectric spectroscopy, differential scanning calorimetry and FTIR spectroscopy. The physical stability of ibuprofen was drastically improved, stabilizing the drug in its amorphous state over a timescale of months. It was found that the polymeric glass transition temperature of the polymer did not correlate with the stabilization effect of ibuprofen. The effect was instead attributed to hydrogen bonding between polymer and ibuprofen. Dispersions using felodipine were however not succesfully prepared.
Keywords: Materialvetenskap; Den kondenserade materiens fysik; Vätskefysik; Materialteknik; Funktionella material; Materials Science; Condensed Matter Physics; Liquid physics; Materials Engineering; Functional materials